Implementation of teaching principles for the development of preschoolers’ creativity through integrated activities in kindergarten - Oana Iuliana ENACHE (ACROSS)
Preschool education provides the foundation for the formation of each individual's personality, facilitating the development of the mental processes necessary for integration in diverse activities, as well as the traits of will and character that support development. Identifying the specific characteristics of creativity at pre-school age and the psycho pedagogical conditions which can stimulate or inhibit its development are essential guidelines for the educational process in nursery schools. The development of creative abilities, however, is achieved as a result of the design and implementation of activities geared to the psychosomatic characteristics of pre-school children, in accordance with the methodological, scientific and teaching aspects specific to the age level. Providing a didactically adapted legislative framework can ensure the success of activities and better results with pre-school children.